Foot plantar pressure measurement system: A review - Abdul Hadi, Abdul Razak; Zayegh, Aladin; Begg, Rezaul K.; Yufridin, Wahab (MDPI, Basel, Switzerland., 2013)
Link to publisher's homepage at http://www.mdpi.com/